Immunogenicity and Tolerance of a 7-Valent Pneumococcal Conjugate Vaccine in Nonresponders to the 23-Valent Pneumococcal Vaccine - Zielen, S. (American Society for Microbiology, 2000)
There is still a lack of effective vaccination strategies for patients with a deficient antibody response to bacterial polysaccharide antigens. In an open trial, we evaluated the immunogenicity and tolerance of a new 7-valent pneumococcal conjugate vaccine in 22 infection-prone nonresponders to pneumococcal polysaccharide vaccine and 21 controls. In the patient group, nonresponsiveness was confirmed by repeated vaccination with a 23-valent pneumococcal polysaccharide vaccine. The study protocol provided two doses of the pneumococcal conjugate vaccine, given 4 to 6 weeks apart, for both groups. The antibody response was determined before each vaccination and on follow-up by an enzyme-linked immunosorbent assay and compared to the response in a functional opsonophagocytosis assay. Patients showed a significantly lower postvaccination immune response for all serotypes than did controls. The postvaccination response was serotype dependent. A median titer of >1 μg/ml in patients was recorded only for serotypes 4, 9V, 14, and 19F, which are known to be more immunogenic than serotypes 6B, 18C, and 23F. In the patient group, 70% responded to serotype 19F (Pnc 19F), 65% responded to Pnc 14 and 4, 60% responded to Pnc 9V, 55% responded to Pnc 18C, 50% responded to Pnc 23F, and 25% responded to Pnc 6B. In the control group >95% of individuals showed a titer of >1 μg/ml to every serotype. The vaccine was tolerated well, and no major side effects have been reported. The new pneumococcal conjugate vaccine is clearly more immunogenic in previous nonresponders than is the 23-valent pneumococcal vaccine. Immunization with a pneumococcal conjugate vaccine should be considered as a strategy to protect high-risk patients.